Modelling the early time behaviour of type Ia supernovae: effects of the Ni-56 distribution - M. R. Magee; S. A. Sim; R. Kotak; W. E. Kerzendorf (EDP SCIENCES S A, 2025)
Recent studies have demonstrated the diversity in type Ia supernovae (SNe Ia) at early times and highlighted a need for a better understanding of the explosion physics as manifested by observations soon after explosion. To this end, we present a Monte Carlo code designed to model the light curves of radioactively driven, hydrogen-free transients from explosion to approximately maximum light. In this initial study, we have used a parametrised description of the ejecta in SNe Ia, and performed a parameter study of the effects of the Ni-56 distribution on the observed colours and light curves for a fixed Ni-56 mass of 0.6 M-circle dot. For a given density profile, we find that models with Ni-56 extending throughout the entirety of the ejecta are typically brighter and bluer shortly after explosion. Additionally, the shape of the density profile itself also plays an important role in determining the shape, rise time, and colours of observed light curves. We find that the multi-band light curves of at least one SNe Ia (SN 2009ig) are inconsistent with less extended Ni-56 distributions, but show good agreement with models that incorporate Ni-56 throughout the entire ejecta. We further demonstrate that comparisons with full UVOIR colour light curves are powerful tools in discriminating various Ni-56 distributions, and hence explosion models.